Using Web-Data to Estimate Spatial Regression Models - Arbia, Giuseppe; Nardelli, Vincenzo (International regional science review, 2024)
Macro econometrics has been recently affected by the so-called ‘Google Econometrics’. Comparatively less attention has been paid to the subject by the regional and spatial sciences where the Big Data revolution is challenging the conventional econometric techniques with the availability of a variety of non- traditionally collected data (such as, e. g., crowdsourcing, web scraping, etc) which are almost invariably geo-coded. However, these unconventionally collected data represent only what in statistics is known as a “convenience sample” that does not allow any sound probabilistic inference. This paper aims at making aware researchers of the consequence of the unwise use of such data in the applied work and to propose a technique to minimize such the negative effects in the estimation of spatial regression. The method consists of manipulating the data prior their use in an inferential context.